Analisa dan Perancangan Aplikasi Marketplace Bagi Pelaku UMKM Untuk Pemulihan dan Kebangkitan Ekonomi di Indonesia Pada Masa Pandemi Covid-19 - Himawan; Kristin Paulina; Aditya Ridwan Fauzi (Systemic: Information System and Informatics Journal, 2021)
The Covid-19 pandemic that hit almost all countries and it also happens in Indonesia, caused a huge impact, especially in the economic, educational, health and social fields. Many countries are experiencing extraordinary crisis due to the long-lasting Covid-19 pandemic. One example of the effect that is felt by almost the entire world community with the Covid-19 pandemic is in the economic field, this situation can be shown by the countless number of business fields that have experienced a crisis and even ended in bankruptcy. However, looking at the situation and the realities of life, business actors are starting to think about utilizing and optimizing the use of digital media, information technology media and also social media. This needs to be done by micro, small and medium enterprises or also known as “UMKM” actors to gradually transform from business forms that previously used conventional models to digitalization models. Through writing this journal, the researchers will propose a model for designing a marketplace application platform that can be used as a medium for “UMKM” actors who are members of the Prosperous Indonesia “UMKM” Cooperative (KOMINDO) to be able to market and sell various products produced by each KOMINDO member.